Financial Sector Assessment Program : Montenegro Deposit Insurance System - World Bank (World Bank, Washington, DC, 2016)
During September 1-15, 2015 an assessment under the IMF/World Bank Financial Sector Assessment Program (FSAP) was conducted for Montenegro. The mission assessed financial sector risks and vulnerabilities, assessed the quality of financial sector supervision, and evaluated financial safety-net arrangements. As part of the FSAP, the deposit insurance system was assessed against the BCBS-IADI Core Principles for Effective Deposit Insurance Systems (CP) from 2009. The revised IADI CP from 2014, which still have to be adopted by the IMF and the World Bank, have been used as a reference in this assessment. The assessment was conducted by a team of experts from the World Bank and IMF. The assessment has the following main findings: The deposit insurance system in Montenegro is relatively well developed. DPF was established in 2006 and operates under the narrow mandate of a pay-box. It is financed by annual premiums from member banks, supported by a standby credit line with the EBRD and a statutory provision for back-up funding from the government. The current level of funding is sufficient to cover the insured deposits in all small banks. The coverage level is EUR 50,000 per depositor per bank and covers natural and legal persons. With this level, DPF insures 99.26 percent of depositors and 36.38 percent of deposits fully. Since its establishment, DPF has developed much of the infrastructure required to ensure prompt payout of deposits, including payout software to reimburse depositors within fifteen working days after a bank failure and a MoU to support information exchange and coordination with CBM. The deposit insurance system has never been triggered.